Sabar Dalam Al-Qur’An Dan Korelasinya Terhadap Kesehatan Mental - Abdul Salam; Rahendra Maya (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study examines the concept of patience (ṣabr) in the Qur'an and its corelation with the mental health of human in facing the dynamics of modern life. In the Qur'anic perspective, patience is not merely understood as self-restraint, but also as spiritual strength, steadfastness of heart, and consistency in performing righteous deeds while avoiding wrongdoing. This research employs a qualitative approach using a library research method, analyzing Qur'anic verses related to patience along with interpretations from classical and contemporary exegetes. The findings indicate that patience encompasses interconnected theological, psychological, and social dimensions. Theologically, patience strengthens the relationship between humans and God; psychologically, it fosters emotional stability and resistance to stress; and socially, it promotes harmony and solidarity within the community. Therefore, the internalization of the value of patience significantly contributes to building both individual and collective mental health, particularly in responding to social pressures, economic crises, and rapid cultural changes. The Qur'anic concept of patience remains relevant as an ethical and spiritual foundation for mental health of human.